2019
DOI: 10.1186/s13073-019-0644-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of custom-designed NGS panel testing in pediatric tumors

Abstract: Background Somatic genetic testing is rapidly becoming the standard of care in many adult and pediatric cancers. Previously, the standard approach was single-gene or focused multigene testing, but many centers have moved towards broad-based next-generation sequencing (NGS) panels. Here, we report the laboratory validation and clinical utility of a large cohort of clinical NGS somatic sequencing results in diagnosis, prognosis, and treatment of a wide range of pediatric cancers. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 50 publications
3
79
0
Order By: Relevance
“…The Ph-like TVA1 cell line was initially created as a childhood Ph-like ALL patient-derived xenograft (PDX) model in immunocompromised mice and subsequently immortalized via in vitro culture (52). Archer fusionplex testing and next-generation sequencing of some cell lines and PDX models were performed at the CHOP Division of Genomic Diagnostics clinical core facility as previously described (64). The Ph-like kinase-activated gene expression signature was confirmed by a validated clinical low-density microarray analysis in relevant ALL cell lines and PDX models as previously described (6,20,65).…”
Section: Methodsmentioning
confidence: 99%
“…The Ph-like TVA1 cell line was initially created as a childhood Ph-like ALL patient-derived xenograft (PDX) model in immunocompromised mice and subsequently immortalized via in vitro culture (52). Archer fusionplex testing and next-generation sequencing of some cell lines and PDX models were performed at the CHOP Division of Genomic Diagnostics clinical core facility as previously described (64). The Ph-like kinase-activated gene expression signature was confirmed by a validated clinical low-density microarray analysis in relevant ALL cell lines and PDX models as previously described (6,20,65).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the use of next-generation sequencing (NGS) platforms for the molecular characterization of solid tumors has gained significant popularity [113,175,209]. These platforms range from approximately 300-500 gene targets (or more) and often include most of those altered in pLGG.…”
Section: Next Generation Sequencing Panelsmentioning
confidence: 99%
“…They leveraged ArcherDx Fu-sionPlex technology (identical to our approach) to identify these cases. Additionally, several recent studies have demonstrated the use of AMP technology (ArcherDx) for identifying rare and complex structural variants in pediatric cancers [32,33]. Taken together, advanced sequencing techniques are required to accurately detect and annotate complex StVs that are commonly associated with pediatric leukemias.…”
Section: Discussionmentioning
confidence: 99%